2004
DOI: 10.1007/s10517-005-0029-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of new wound dressings on healing of thermal burns of the skin in acute radiation disease

Abstract: Effects of new wound dressing bacterial cellulose impregnated with SOD and poviargol (Procel-Super and Procel-PA) and Inerpan hydrogel dressing on the reparative processes in deep dermal burns (IIIa-IIIb degree) in rats exposed to total even irradiation in a dose of 4 Gy were studied. Inerpan and Procel-Super dressings proved to be the most effective under these conditions: they accelerated healing of burn wounds by 17.0 and 5.5%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…For example, Legeza et al created a microbial cellulose wound dressing for the treatment of thirddegree burns that was impregnated with superoxide dismutase (an antioxidant) or poviargol (an antibiotic) in order to augment its therapeutic properties. 55 A study by Ciechanska showed that an MC-chitosan composite material could be created during the synthesis of the cellulose membrane by adding chitosan to the culture medium. 56 In other words, the glucosamine and N-acetylglucosamine units were incorporated into the synthesized cellulose chains, which was demonstrated in another study by Shirai et al 57 Ciechanska claims that such a composite material has improved biological and physical properties.…”
Section: Microbial Cellulose As a Wound-healing Systemmentioning
confidence: 99%
“…For example, Legeza et al created a microbial cellulose wound dressing for the treatment of thirddegree burns that was impregnated with superoxide dismutase (an antioxidant) or poviargol (an antibiotic) in order to augment its therapeutic properties. 55 A study by Ciechanska showed that an MC-chitosan composite material could be created during the synthesis of the cellulose membrane by adding chitosan to the culture medium. 56 In other words, the glucosamine and N-acetylglucosamine units were incorporated into the synthesized cellulose chains, which was demonstrated in another study by Shirai et al 57 Ciechanska claims that such a composite material has improved biological and physical properties.…”
Section: Microbial Cellulose As a Wound-healing Systemmentioning
confidence: 99%
“…Bacterial cellulose impregnated membranes and poviargol, an antiseptic substance containing silver, was shown to accelerate the healing of irradiated wounds in an animal model [39]. A recent animal study has revealed that silver nanoparticles have the potential to promote wound healing through accelerated re-epithelialization and enhanced differentiation of fibroblasts.…”
Section: Future Aspects In the Treatment Of Irradiated Woundsmentioning
confidence: 99%
“…Legeza et al [75] produced a BC wound dressing for the treatment of third degree burns that is impregnated with superoxide dismutase (an antioxidant) or poviargol (an antibiotic).…”
Section: Bc Based Structures For Biomedical Applicationsmentioning
confidence: 99%